Using the Past and Bridging the Gap: Premodern Islamic Legal Texts in New Media. (12th November 2018) - Kooria, Mahmood
Abstract : This article analyses the internal dynamics of online Islamic legal discourses embedded in their offline and multimedia contexts that use of a rich repository of legal texts composed over a period of about a thousand years. Through their vigorous and spirited engagements with these historical texts, contemporary Islamic jurists simultaneously create new digital platforms in mass and social media to disseminate their ideas. In so doing, they perpetuate a long textual legal tradition through hypertext commentaries and super-commentaries. The premodern texts are thus reborn through new forms of ḥāshiya s such as audio commentaries, video commentaries, audio-video commentaries and hypertext commentaries. These new developments from the age of new media contribute to the textual longue-durée of Islamic law. Tracking the peregrinations of three Islamic legal texts in the mass media and cyber world, I argue that the dissemination of premodern Islamic legal texts via cyber space has resulted in the "democratization" of a knowledge-system that was previously dominated by trained fuqahā and affiliated institutional structures and has enlivened the traditional school affiliations.